Gender equity and decision-making patterns in family-related activities of the Aklanon rural mothers - Israel, Perlita R.; Mayo, Adelaida V. (2008)
The study examined gender equity and decision-making patterns of the Aklanon rural mothers and their partners and determine the factors related to power in decision-making. The decision-making patterns in the family was ascertained in terms of the family-related activities such as parenting, educating family members, family budgeting, family nutrition and health; and in terms of family practices on spousal rights, benefits, obligations and opportunities. Three hundred and eighty-eight (388) Aklanon mothers belonging to dual-earner households from eight selected municipalities in the province of Aklan, Philippines, responded to the researcher-made questionnaire. Chi-square and averaging coefficient were applied to determine the correlation between mothers profile and gender equity in the family decision-making patterns. The findings revealed that husbands and wives made joint decision in terms of parenting, education family members, budgeting and family health and nutrition. The same trend was observed when making decisions on family practices. Both husbands and wives commonly enjoy rights, benefits, obligations and opportunities in the family. There was no significant correlation found between the personal and family-related factors and decision-making patterns of rural mothers. Rural mothers, compared to their husbands, play a unique and more significant role in the family in terms of parenting, budgeting and educating family members. They are less dominant in the household but are not totally passive. Rural earning mothers have been found to have a voice in the family. They have accepted the situation where their husbands make the decisions but they also make negotiations in order to reach an agreement or compromise.
Keywords: Decision making; Gender differences (Psychology); Family roles